PV Energy Generation Assessment based Si-crystalline and CIS Technologies under Algerian Climatic Conditions - Aziz, Haffaf Haffaf; Lakdja, Fatiha (جامعة الوادي - university of el oued, 2022)
As in the whole world, renewable energies in Algeria, including photovoltaic energy, are attracting more and more attention in recent years. The integration of distributed generation (DG) into the power grid using renewable energy sources, such as PV, FC and wind, has important advantages such as low distribution losses, better continuity and power quality, and high system reliability. This paper is about a simulation study to analyze the energy assessment of a grid-connected photovoltaic system (GCPVS). The system with 1 MW capacity is simulated and analyzed based on solar resource, tilt and azimuth angles for each area and using Si-crystalline and CIS technologies under different weathers conditions in Algeria (Algiers, Chlef, Tlemcen, Tamanrasset and El Oued). The system configuration is simulated using the new version of PVGIS to account for PV plant energy output assessment. The obtained simulation results were discussed as per monthly and yearly values based on PV cell technologies and optimized tilt and azimuth angle.
Article
Keywords: Solar energy, PV energy assessment, PV grid-connected, PV cells Technologies, PVGIS tool